Verticle decentralization and urban service delivery in South Africa: Does politics matter? - Robert Cameron (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This study examines the role of politics on decentralization and service delivery in South Africa, with a specific focus on Johannesburg and Cape Town. The research delineates how national decentralization has affected service delivery responsibilities and resources, determines whether service delivery is affected by whether or not a city is governed by an opposition party, and considers what the nature of inter-governmental relations implies for donors operating in South Africa's urban sector. The study finds that service delivery does not appear to be worse off in Cape Town than in Johannesburg, even though the former is controlled by the opposition Democratic Alliance while the latter is in the hands of the ruling African National Congress. While there have been political attempts to undermine opposition-controlled Cape Town, the fiscal elements are protected by a relatively strong and well-managed department of finance. Moreover, both donors and the national government steer money towards Cape Town because they know it can deliver on its obligations.
Keywords: D72; H70; N47; O18; 330; decentralization; party politics; service delivery; South Africa; urbanization; Kommunale Dienstleistung; Dezentralisierung; Südafrika; Johannesburg; Kapstadt